Metformin Alters the Chemotaxis and Flagellar Motility of Escherichia coli - Ye, Yingxiang; Jiang, Panmei; Huang, Chengyun; Li, Jingyun; Chen, Juan; Wang, Lu; Lin, Yan; Wang, Fangbin; Liu, Jian (Frontiers in Microbiology, 2022)
Metformin is a biguanide molecule that is widely prescribed to treat type 2 diabetes and metabolic syndrome. Although it is known that metformin promotes the lifespan by altering intestinal microorganism metabolism, how metformin influences and alters the physiological behavior of microorganisms remains unclear. Here we studied the effect of metformin on the behavior alterations of the model organism Escherichia coli (E. coli), including changes in chemotaxis and flagellar motility that plays an important role in bacterial life. It was found metformin was sensed as a repellent to E. coli by tsr chemoreceptors. Moreover, we investigated the chemotactic response of E. coli cultured with metformin to two typical attractants: glucose and α-methyl-DL-aspartate (MeAsp), finding that metformin prolonged the chemotactic recovery time to the attractants, following by the recovery time increased with the concentration of stimulus. Metformin also inhibited the flagellar motility of E. coli including the flagellar motor rotation and cell swimming. The inhibition was due to the reduction of torque generated by the flagellar motor. Our discovery that metformin alters the behavior of chemotaxis and flagellar motility of E. coli could provide potential implications for the effect of metformin on other microorganisms.